ANALISIS USAHATANI NENAS DI KECAMATAN TAMBANG KABUPATEN KAMPAR - Ilma Satriana Dewi; Darus; Bagus Prasetyo (UIR Press, 2021)
It is possible to further develop pineapple cultivation in the Tambang sub-region. High production of pineapple during the main harvest often causes the price of pineapple to fall. This can affect the income of pineapple farmers. The purpose of this work is to analyze the characteristics of pineapple growers and profiles of pineapple farming and to analyze the use of inputs, production, prices, income and efficiency of pineapple farming. Quantitative and qualitative descriptive analysis and farm income analysis were used as data analysis. The results showed that the characteristics of pineapple farmers from the type of work, pineapple farming was the main occupation, the average age was 49.75 years (productive age), the average education was elementary school graduation, the number of families was 3-4 people and the average experience was 15.7 years. The pineapple farm profile with land holdings is owned, the average land area was 1.26 ha. Business terms are still implemented in a simple (traditional) way. The use of production facilities per field area per month was 2,925 plant seeds, 265 kg of urea fertilizer, 70.25 kg of KCl, 3.05 kg of NPK Phonska, 15 kg of TSP, 25 ml of pesticides, 9.5 ml of ethyl. Equipment use consisted of using chopping knife, sickles, hand sprayers, and baskets. The number of employees was 15.5 HOK/cultivated area/month. The average fixed price was Rp. 170,270/cultivated area/month, the average variable cost was Rp. 4,291,792.7/cultivated area/month, the average production was 1,962 pcs/month, the average turnover was Rp. 7,904,500/cultivated area/month, the average profit was Rp. 3,442,438/field/month and the efficiency of pineapple farming was 1.8.